The Role of Autonomy on Students' Creativity in Writing Short Story: A Narrative Inquiry - Sulastri, Fera; Narulita Dewi, Nita Sari (Universitas Siliwangi, 2019)
Learning autonomy offers a lot contribution to students' successful learning since it is the ability of learners to take control of their learning goal and management. One of this characteristics influences how students set their learning management based on what they are interested in. This situation builds creative atmosphere since students set their goal, management, style, and preferences. In writing a story, students need creativity to make an interesting story. Therefore, this study distinguishes a student gaining the best story in children's literature class. It is specifically aimed at investigating how autonomous the student is so that it came to her creativity in creating the story. The data are collected from documentation, student's reflective journals, and also some interviews. The method of this study is narrative inquiry while thematic analysis is used for analyzing the data. The result shows that the student becomes autonomy by having these characteristics; (1) having learning management, (2) Intrinsically motivated, (3) Knowing personal strength and weakness. Those characteristics have important role in bringing the student to be successful learner